2016
DOI: 10.14444/3001
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Societal Costs of Anterior Discectomy and Fusion (ACDF) versus Cervical Disc Arthroplasty (CDA) for Treatment of Cervical Radiculopathy

Abstract: Background Current literature suggests that anterior cervical discectomy and fusion (ACDF) and cervical disc arthroplasty (CDA) have comparable clinical outcomes for the treatment of cervical radiculopathy. Given similar outcomes, an understanding of differences in long-term societal costs can help guide resource utilization. The purpose of this study was to compare the relative long-term societal costs of anterior cervical discectomy and fusion (ACDF) to cervical disc arthroplasty (CDA) for the treatment of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…A study of 60 consecutive cervical radiculopathy patients found that CDR was associated with similar improvements in VAS-neck pain and Short-Form 12 questionnaire compared with ACDF, however cost-effectiveness was best with ACDF with cage alone [26]. Interestingly, one economic and decision analysis found that for radiculopathy patients, CDR resulted in lower long-term costs compared with ACDF [27]. Finally, a cohort study of CDR compared with posterior microendoscopic laminoforaminotomy for radiculopathy patients found no significant difference in improvements in NDI, VAS-neck pain, or VAS-arm pain at 3-, 6-, 12-, and 24-month follow-up [28].…”
Section: Discussionmentioning
confidence: 99%
“…A study of 60 consecutive cervical radiculopathy patients found that CDR was associated with similar improvements in VAS-neck pain and Short-Form 12 questionnaire compared with ACDF, however cost-effectiveness was best with ACDF with cage alone [26]. Interestingly, one economic and decision analysis found that for radiculopathy patients, CDR resulted in lower long-term costs compared with ACDF [27]. Finally, a cohort study of CDR compared with posterior microendoscopic laminoforaminotomy for radiculopathy patients found no significant difference in improvements in NDI, VAS-neck pain, or VAS-arm pain at 3-, 6-, 12-, and 24-month follow-up [28].…”
Section: Discussionmentioning
confidence: 99%
“…Three prospective economic evaluations [48,58,66] were included; all others were retrospective CEAs or CUAs. In a total of 5 studies, a Markov Analysis was performed [44,45,47,51,56].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The six remaining studies described costs without (surgical) cohort [51,54,57] or compared auto-and allograft techniques for ACDF, but costs are represented separately [Table 1] [52, 53,55]. There was a large variety in the evaluated study populations, as some studies only included patients with radiculopathy [46,47,49,51,53] or myelopathy [48,66], and other studies specifically evaluated singlelevel surgeries [46,49,54,55,59,63,69,70] in contrast to those that only assessed multi-level surgeries [43,48,56,61,64].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…89 Although there are limited reports using indirect costs from a societal perspective, Ghori et al demonstrated that ACDF was more expensive in the long-term with costs of $31,780 compared to $24,119 for patients aged 45 to 65 years old, and taking into consideration loss of productivity and reoperation rates. 90,91 Ament et al also demonstrated that CDA was the leading intervention with an ICER of -$165,103 per QALY when considering indirect costs and using $50,000 as the threshold for WTP at 5 year follow-up. 84 These results suggest that CDA is more cost-effective when considering decreased productivity loss and increased return-to-work compared to ACDF.…”
Section: Comparison Of Cost-effectiveness Between Acdf and Cdamentioning
confidence: 99%